2013
DOI: 10.1017/s1041610213001506
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Caregiver Guilt Questionnaire (CGQ) in a sample of British dementia caregivers

Abstract: The replication of the five-factor structure suggests that these are relevant themes within the feelings of guilt to both Hispanic and British dementia caregivers. The CGQ has been demonstrated to be a valid measure for use with British dementia caregivers and is likely to be of use in clinical and research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 24 publications
(78 reference statements)
3
28
1
3
Order By: Relevance
“…The goal of this study was to analyse the role of ambivalence and guilt feelings as contributors to caregivers' depressive symptomatology. Although the associations between depressive symptoms and ambivalence (Losada et al, ) and guilt feelings (Losada et al, ; Roach et al, ) have been reported in previous research, this study offers the first evidence of the pathways through which they are linked with caregivers' depressive symptomatology. Specifically, we found that the significant correlation between frequency of and reaction to disruptive behaviours with caregivers' depressive symptomatology became insignificant when other variables (ambivalence and guilt feelings) were controlled.…”
Section: Discussionsupporting
confidence: 61%
“…The goal of this study was to analyse the role of ambivalence and guilt feelings as contributors to caregivers' depressive symptomatology. Although the associations between depressive symptoms and ambivalence (Losada et al, ) and guilt feelings (Losada et al, ; Roach et al, ) have been reported in previous research, this study offers the first evidence of the pathways through which they are linked with caregivers' depressive symptomatology. Specifically, we found that the significant correlation between frequency of and reaction to disruptive behaviours with caregivers' depressive symptomatology became insignificant when other variables (ambivalence and guilt feelings) were controlled.…”
Section: Discussionsupporting
confidence: 61%
“…(), Roach et al . () and van der Lee et al . () by identifying how a range of psychosocial factors influence BPSD‐related distress individually and in combination, by conducting multiple analyses with a large sample size.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, competence was found to have significant negative correlations with burden and BPSD‐related distress and was found to significantly negatively predict burden and BPSD‐related distress (van der Lee et al ., ). Greater levels of guilt made a significant contribution to caregiver burden (Gonyea et al ., ), and guilt was found to significantly correlate with burden (Roach et al ., ).Moreover, psychosocial factors such as the caregiving relationship, rather than the characteristics of the person with dementia (Iecovich, ), were associated with caregiver stress and burden (Steadman et al ., ). A lack of closeness was found to be associated with increased distress in the caregiver (Williamson & Schulz, ), which may have been due to the guilt the caregiver experienced about no longer loving the person with dementia (Jarret, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When informal caregivers feel that the care is not sufficient, this may lead to feelings of burn out, depression, and guilt. (Almberg, Grafström, & Winblad, 1997, Collins & Jones, 1997Donaldson, Tarrier, & Burns, 1998;Edwards & Scheetz, 2002;Ekwall & Hallberg, 2007;Gonyea, Paris, & De Saxe Zerden, 2008;Madsen & Birkelund, 2013;Roach, Laidlaw, Gillanders & Quinn, 2013;Springate & Tremont, 2014) In particular, cognitive problems of the care recipient are related to an increased complexity of the care and increased burden of the informal caregiver (Fowler, Fisher, & Pitts, 2014;Nordtug & Holen, 2011;Sequiera, 2013;Wenzel & Poynter, 2014). Apart from stress, problems in the social and relational domain occur, (Feinberg & Whitlatch, 2002), especially when the care recipient has cognitive problems (Harris, 2013;Luchetti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%